Enlarged Perivascular Spaces in the Basal Ganglia Independently Related to Gait Disturbances in Older People With Cerebral Small Vessel Diseases - Yang, Shuna; Li, Xuanting; Hu, Wenli; Qin, Wei; Yang, Lei (Frontiers in Aging Neuroscience, 2022)
Background and Objective: Gait disturbances are common in the older people and are associated with adverse consequences, e.g., falls and institutionalization. Enlarged perivascular spaces in the basal ganglia (BG-EPVS) are considered an MRI marker of cerebral small vessel diseases (CSVD). However, the consequences of BG-EPVS are largely unknown. Previous studies showed that other CSVD markers were related to gait disturbances. However, the relation between BG-EPVS and gait performance is unclear. Therefore, we aimed to explore the relation between BG-EPVS and gait performance in elderly individuals. Methods: We recruited the older people with CSVD in Neurology Department of our hospital from December 1, 2020 to October 31, 2021. Participants with BG-EPVS > 20 on the unilateral side of the basal ganglia slice containing the maximum number were classified into the BG-EPVS group (n=78), the rest were classified into the control group (n=164). Quantitative gait parameters and gait variability were provided by the IDEEA gait analysis system. Semiquantitative gait assessment was measured with Tinetti test. Point-biserial and multivariate linear regression analysis were performed to investigate the association between BG-EPVS and gait performance. Results: The BG-EPVS group had a lower gait speed and cadence, shorter stride length, longer stance phase percentage, smaller pre-swing angle and foot fall, and lower Tinetti gait test and balance test scores compared with those in the control group (P＜0.05). There were no statistical differences in stride length variability and stride time variability between the two groups (P＞0.05). Pearson correlation analysis showed that BG-EPVS were negatively related to gait speed, cadence, stride length, pre-swing angle and foot fall (γrange=-0.497 to -0.237, P＜0.001), and positively related to stance phase percentage (γ=0.269, P＜0.001). BG-EPVS were negatively related to the score of the Tinetti gait test (γ=-0.449, P＜0.001) and balance test (γ=-0.489, P＜0.001). Multiple linear regression analysis indicated that BG-EPVS was an independent risk factor for gait disturbances and poor balance after adjusting for confounders, including other CSVD markers. Conclusion: Large numbers of BG-EPVS were independently related to gait disturbances in older people with CSVD. This finding provides information about the consequences of BG-EPVS and risk factors for gait disturbances.